Pengaruh Literasi Keuangan, Inklusi Keuangan, dan Sikap Keuangan terhadap Pengelolaan Keuangan UMKM di Kapanewon Godean, Kabupaten Sleman - Kusumaningrum, Sintawati Mita; Wiyono, Gendro; Maulida, Alfiatul (Jurnal Samudra Ekonomi dan Bisnis, 2023)
The study aims to determine the effect of financial literacy, financial inclusion, and financial attitude on MSME financial management in Kapanewon Godean. The sample used amounted to 99 respondents. The sampling technique used purposive sampling method. Analysis of research data using multiple linear regression method. The results indicate that financial literacy has a negative and significant effect on financial management, financial inclusion has no effect on financial management, and financial attitude has a positive and significant effect on financial management. The other results state that financial literacy, financial inclusion, and financial attitude simultaneously influence MSME financial management in Kapanewon Godean. The results of this study serve as a reference for the local government of Sleman Regency in planning a strategy for improving the performance of MSMEs.